Considering the plug-flow behavior of the gas phase in nitrifying BAF models significantly improves the prediction of N2O emissions. (1st June 2019) - Fiat, Justine; Filali, Ahlem; Fayolle, Yannick; Bernier, Jean; Rocher, Vincent; Spérandio, Mathieu; Gillot, Sylvie
Abstract: Nitrifying biologically active filters (BAFs) have been found to be high emitters of nitrous oxide (N2 O), a powerful greenhouse gas contributing to ozone layer depletion. While recent models have greatly improved our understanding of the triggers of N2 O emissions from suspended-growth processes, less is known about N2 O emissions from full-scale biofilm processes. Tertiary nitrifying BAFs have been modeled at some occasions but considering strong simplifications on the description of gas-liquid exchanges which are not appropriate for N2 O prediction. In this work, a tertiary nitrifying BAF model including the main N2 O biological pathways was developed and confronted to full-scale data from Seine Aval, the largest wastewater resource recovery facility in Europe. A mass balance on the gaseous compounds was included in order to correctly describe the N2 O gas-liquid partition, thus N2 O emissions. Preliminary modifications of the model structure were made to include the gas phase as a compartment of the model, which significantly affected the prediction of nitrification. In particular, considering gas hold-up influenced the prediction of the hydraulic retention time, thus nitrification performances: a 3.5% gas fraction reduced ammonium removal by 13%, as the liquid volume, small in such systems, is highly sensitive to the gas presence. Finally, the value of the volumetric oxygen transfer coefficient was adjusted to successfully predict both nitrification and N2 O emissions. Graphical abstract: Image 1 Highlights: A nitrifying BAF model was extended to describe full-scale N2 O emissions. Inclusion of a mass balance for the gas phase is essential to describe N2 O emissions. Gas phase assumptions heavily impacted the prediction of nitrifying performances. The calibrated model successfully described nitrification and the mass transfer of O2 and N2 O.